Characterization and Experimental Analysis of AA7075 Aluminium Alloy and Rice Husk Ash Reinforced Hybrid Composite - Sulayman, F. A.; Saraki, Y. A.; Sulaiman, I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Abstact